2016
DOI: 10.1101/lm.040485.115
|View full text |Cite
|
Sign up to set email alerts
|

The potential of epigenetics in stress-enhanced fear learning models of PTSD

Abstract: Prolonged distress and dysregulated memory processes are the core features of post-traumatic stress disorder (PTSD) and represent the debilitating, persistent nature of the illness. However, the neurobiological mechanisms underlying the expression of these symptoms are challenging to study in human patients. Stress-enhanced fear learning (SEFL) paradigms, which encompass both stress and memory components in rodents, are emerging as valuable preclinical models of PTSD. Rodent models designed to study the long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 169 publications
(224 reference statements)
0
26
0
Order By: Relevance
“…social hierarchy, stress adaptability). DNA methylation and histone modifications have been studied in the stress (68) and memory fields (13), and epigenetic interactions are likely after successive stressful events to confer resilience or susceptibility (27). Epigenetics may also impart gender-specific extinction impairments, as expression of DNA methyltransferase 3a confers resilience to “depression” in a variable stress paradigm (69).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…social hierarchy, stress adaptability). DNA methylation and histone modifications have been studied in the stress (68) and memory fields (13), and epigenetic interactions are likely after successive stressful events to confer resilience or susceptibility (27). Epigenetics may also impart gender-specific extinction impairments, as expression of DNA methyltransferase 3a confers resilience to “depression” in a variable stress paradigm (69).…”
Section: Discussionmentioning
confidence: 99%
“…These manipulations induce their own neuromolecular changes, precluding studies of the mechanisms underlying the genesis and perpetuation of the PTSD-like phenotype. Furthermore, outbred lines are used in all cases of differential susceptibility, limiting the ability to isolate epigenetic contributors, which are expected to be highly relevant to individual variability in susceptibility (27–30). Here we present a protocol that addresses these challenges, while retaining the behavioral phenotypes and neurochemical dysregulation demonstrated by existing PTSD-like models.…”
Section: Introductionmentioning
confidence: 99%
“…Animals exposed to these stressors exhibit characteristics that reflect those generally observed in PTSD, such as increased anxiety-like behaviors, exaggerated startle, and abnormal GC response (i.e., reduced basal GC levels and enhanced GC negative feedback), indicating that they may be appropriate for investigating psychological, trauma-induced cognitive/behavioral and neuroendocrine alterations 17,77,78 . In particular, animal models of PTSD that expose animals to trauma/stressor(s) before fear conditioning show greater face, construct, and predictive validity for PTSD than fear conditioning alone 62,75 , and can be used to determine the epigenetic effect of stress on subsequent fear learning 63 . In conjunction with our understanding from studies that investigated neuroepigenetics of stress and fear memory independently, epigenetic investigations using paradigms such as stress-enhanced fear learning (SEFL) should elucidate distinct mechanisms underlying the interaction between these two major facets of PTSD and have special promise for identifying mechanisms underlying resistance to extinction learning and the role of the BDNF pathway, which is widely implicated in both stress and fear memory 63 .…”
Section: Neuroepigenetic Regulation Of Fear Learning and Memorymentioning
confidence: 99%
“…Moreover, histone acetylation, especially in hippocampal H3 (Levenson et al 2004) and H4 (Peleg et al 2010), as well as amygdalar histone trimethylation of H3K4 (Gupta et al 2010), have been found to also promote fear encoding. Extensive reviews describing the involvement of epigenetic mechanisms in fear memory formation have been performed by Roth et al (2010), Zovkic et al (2013), Kwapis and Wood (2014), Rudenko and Tsai (2014), and Blouin et al (2016).…”
Section: R18mentioning
confidence: 99%